Perjalanan Batin Seniman di Wilayah Malang Raya Pasca-G30s PKI: Pendekatan Konflik Kurt Lewin - Ella Jayahuda Prasety; Dewa Agung Gede Agung (Universitas Hamzanwadi, 2023)
This research was conducted to analyze the inner conflicts of artists in Malang Raya after the G30S PKI. The data in this study are described based on conflict theory according to Kurt Lewin as; (1) conflict between approaches, (2) conflict between approaches, and (3) conflict between approaches and the factors that cause inner conflict. The results were analyzed based on Abraham Maslow's theory of human needs. This research method is descriptive qualitative using a psychological approach and interview techniques. The results of the study describe the conflicting forms of approaches marking the happiness of artists who survived the G30S incident. The conflict between circumcision and circumcision marks the attitude of the artist who honestly admits his anxiety when he meets a servant of the state. Approach-avoidance conflict is marked when an artist faces two very dilemmatic choices about continuing his work and there is a possibility of not surviving or looking for another job. All of these conflicts arose because the impact of G30S among them was very traumatic.